2015
DOI: 10.11152/mu.2013.2066.173.wly
|View full text |Cite
|
Sign up to set email alerts
|

Does corticosteroid therapy impact fetal pulmonary artery blood flow in women at risk for preterm birth?

Abstract: Aim: Maternal corticosteroid administration in pregnancy is known to enhance fetal lung maturity in at risk fetuses. The aim of this study was to test the hypothesis that corticosteroid therapy alters fetal pulmonary blood flow in pregnancies at risk for preterm birth (PTB). Material and methods: We prospectively evaluated main fetal pulmonary artery (MPA) blood flow in pregnant women at risk for PTB and treated with corticosteroids (betamethasone), compared to an uncomplicated cohort without steroid therapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 8 publications
(20 reference statements)
1
8
0
2
Order By: Relevance
“…We evaluated the impact of steroid therapy on fetal PA and UA indices and whether there was a difference in the fetuses who developed RDS and those who did not. Similar to Lindsley et al, 15 we did not find a statistically significant difference in pulmonary blood flow between fetuses who developed RDS and those who did not. Also, Kim et al 5 reported that there were no significant differences in PA PI and RI scores between fetuses who developed RDS and those who did not.…”
Section: Discussionsupporting
confidence: 90%
“…We evaluated the impact of steroid therapy on fetal PA and UA indices and whether there was a difference in the fetuses who developed RDS and those who did not. Similar to Lindsley et al, 15 we did not find a statistically significant difference in pulmonary blood flow between fetuses who developed RDS and those who did not. Also, Kim et al 5 reported that there were no significant differences in PA PI and RI scores between fetuses who developed RDS and those who did not.…”
Section: Discussionsupporting
confidence: 90%
“…This increase provides a critical developmental trigger, one that is essential for normal maturation of the fetal lung and developmental switching in many other organ systems, including the thyroid, kidney, brain and pituitary (Fowden & Forhead, 2004;Moisiadis & Matthews, 2014). Pregnant women at risk of preterm delivery need to be treated with exogenous glucocorticoids to promote the same results as in the normal intrauterine conditions for fetal development (Gyamfi-Bannerman et al, 2016;Lindsley et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Betamethasone (BM), a synthetic glucocorticoid, is considered the glucocorticoid of choice for this antenatal treatment (Alexander et al, 2016;Lindsley et al, 2015) being used for pregnant women between 24 and 34 weeks of gestation ( Jobe & Soll, 2004;Rayburn et al, 1997;Wapner, 2013), promoting fetal lung maturation and thus reducing the incidence of respiratory distress syndrome, neonatal mortality and morbidity (Gyamfi-Bannerman et al, 2016;Lindsley et al, 2015). However, the prenatal exposure to BM demonstrated several systemic long-term deleterious effects on offspring in different experimental protocols (Alexander et al, 2016;Belanoff et al, 2001;Bertram & Hanson, 2002;Pascual et al, 2014;Su et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Endogenous glucocorticoids are essential for normal maturation of the fetal brain and lung as well as developmental switching in the pituitary, thyroid gland, and kidney . When the risk of preterm delivery persists, a pregnant woman needs to be treated with exogenous glucocorticoids to promote differentiation and maturation of fetal organ systems and to mimic normal intrauterine conditions . Moreover, glucocorticoid application is routine in the prevention and management of conditions that threaten maternal and fetal health, such as maternal asthma and autoimmune diseases . Dexamethasone (Dx) is considered to be the glucocorticoid of choice for antenatal therapy .…”
Section: Introductionmentioning
confidence: 99%